Stability of HIV/HTLV co-infection model with effective HIV-specific antibody immune response - M.A. Alshaikh; N.H. AlShamrani; A.M. Elaiw (Results in Physics, 2021)
This paper presents two HIV/HTLV co-infection models with antibody immune response. The first model is given by 5-dimensional ODEs that describe the within–host interactions of five compartments, susceptible CD4+T cells, HIV-infected cells, HTLV-infected cells, free HIV particles and HIV-specific antibodies. In the second model, we incorporate both silent HIV-infected cells and silent HTLV-infected cells. For both models we address the properties of the solutions, then we investigate the global stability of the steady states. Our global stability results are based on constructing Lyapunov functions and using LaSalle’s invariance principle. To support our theoretical results we conduct some numerical simulations.